2014
DOI: 10.9755/ejfa.v26i1.17447
|View full text |Cite
|
Sign up to set email alerts
|

Microscopical analysis of in vitro Mokara Broga Giant orchids PLBs

Abstract: Mokara orchids comes with variety of hybrids that have unique and highly variable types of characteristics such as petal colour, shape, size and other floral characteristics that make it very important economically and aesthetically. This study was conducted to evaluate on its histological and scanning electron microscopy analyses that make its PLBs to be a desirable biotechnological explant in propagation of this orchid as well as its importance in many biotechnological researches. Histological observation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Orchids belong to the family Orchidaceae with 20,000 to 30,000 species and is the largest family of monocotyledonous that are undoubtedly recognized as economically important flowering plants in the floriculture industry (Antony et al, 2014;Godo et al, 2010). For continued reproduction in nature, orchids require a combination of multiplicity of factors.…”
Section: Introductionmentioning
confidence: 99%
“…Orchids belong to the family Orchidaceae with 20,000 to 30,000 species and is the largest family of monocotyledonous that are undoubtedly recognized as economically important flowering plants in the floriculture industry (Antony et al, 2014;Godo et al, 2010). For continued reproduction in nature, orchids require a combination of multiplicity of factors.…”
Section: Introductionmentioning
confidence: 99%
“…2C). Antony et al (2014) used histological and SEM observations to report that PLBs can develop from a wounded surface of an explant and can be converted into plantlets, as the PLBs consisted of multiple meristematic centers then can be gradually differentiated into shoot, leaf, and root. Our results support the various other reports that demonstrated that PLBs can form from the epidermal cell layers Chang, 2004, 2006;Khoddamzadeh et al, 2011;Kuo et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Leaf explants are easy to obtain, are more expendable to the mother plant (Chugh et al, 2009;De and Sil, 2015), and are available in any season, unlike inflorescence explants (Chugh et al, 2009). Presently, commercial growers of most orchid genera prefer propagation through PLB formation because of the large number of PLBs that can be achieved within a relatively short period of time using this method (Antony et al, 2014;Ng et al, 2010). Plant regeneration through PLB induction from leaf explants has been developed for Acampe (Nayak et al, 1997), Aerides (Murthy, 2005;Murthy and Pyati, 2001), Coelogyne (De and Sil, 2015), Dendrobium (Chung et al, 2005(Chung et al, , 2007Goswami et al, 2015;Martin and Madassery, 2006), Oncidium (Balilashaki et al, 2015;Chen and Chang, 2001, 2004Chen and Hong, 2012;Chen et al, 1999;Chung et al, 2010;Hong et al, 2008;Mata-Rosas et al, 2011;Mayer et al, 2010;Mengxi et al, 2011), Phalaenopsis Gow et al, 2009;Kuo et al, 2005;Park et al, 2002aPark et al, , 2002b, Spathoglottis (Teng et al, 1997), Vanda (Decruse et al, 2003), and Vanilla (Janarthanam and Seshadri, 2008;Tan et al, 2011).…”
mentioning
confidence: 99%
“…Since 1970's, different biotechnological approaches e.g. in vitro micropropagation, genetic transformation, cryopreservation and hybridization techniques are widely used for orchid improvement (Antony et al 2014). Those techniques are essential tools to meet the commercial demand and conservation of wild, rare and useful orchid species in the world.…”
Section: Introductionmentioning
confidence: 99%